Nilai-Nilai Pendidikan Karakter Dalam Film Buya Hamka Sebagai Pengayaan Pembelajaran Sejarah - Sadito, Aqsal; Galuh, Dimas (SEUNEUBOK LADA: Jurnal ilmu-ilmu Sejarah, Sosial, Budaya dan Pendidikan, 2025)
Pancasila serves as the foundational philosophy and guiding principle of Indonesian society, encompassing essential values of character education. One medium that can be utilized as an instrument for instilling these values is film. This study aims to elaborate on the character values derived from Pancasila as represented in the film Buya Hamka Volume 1. The research employs a library-based method within a qualitative paradigm. The research procedure includes determining the object of analysis, collecting relevant data and information, categorizing findings descriptively, drawing conclusions regarding character values, and examining their implications for education. The findings indicate that the character values exemplified by Buya Hamka in the film include critical thinking, communicative competence, religiosity, patriotism, tolerance, responsibility, and creativity. Accordingly, this study concludes that the application of Pancasila-based values is highly compatible with the principles of character education. It is expected that the integration of these values will contribute to shaping the character of the younger generation as future leaders and successors of the nation.